Structure of cell walls in yeast and other fungi - Lipke, Peter (Henry Stewart Talks, 2022)
Fungal cell walls, Glycans, S. cerevisiae, C. albicans, Mannose, Chitin, Glycan biosynthesis, Mannoproteins, GPI-crosslinked proteins, N. crassa, Yeast cell wall dynamics, Cell wall conservation and evolution